2005
DOI: 10.1111/j.1365-2672.2005.02643.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed ultrasound in combination with gentamicin on bacterial viability in biofilms on bone cements in vivo

Abstract: Aims: The aim of this study is to investigate whether pulsed ultrasound (US) in combination with gentamicin yields a decreased viability of bacteria in biofilms on bone cements in vivo. Methods and Results: Bacterial survival on bone cement in the presence and absence of ultrasound was compared in a rabbit model. Two bone cement samples with an Escherichia coli ATCC 10798 biofilm were implanted in a total of nine rabbits. In two groups bone cement discs loaded with gentamicin, freshly prepared and aged were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 32 publications
3
57
0
Order By: Relevance
“…The viability of Escherichia coli biofilms has also been significantly reduced in vivo using pulsed low frequency ultrasound (25% duty, power intensity 500 mW/cm 2 for a treatment period of 24 or 48 h) in combination with gentamicin but these effects were not reproducible against Pseudomonas aeruginosa biofilms [89][90][91]. In 2005, Ensing et al [92] also demonstrated greater than 50% reductions in the viability of Escherichia coli biofilms by combining pulsed ultrasound treatment (24-48 kHz, power intensity 500 mW/cm 2 ) with gentamicin.…”
Section: Biofilm Prevention and Control Using Acoustic Energymentioning
confidence: 99%
“…The viability of Escherichia coli biofilms has also been significantly reduced in vivo using pulsed low frequency ultrasound (25% duty, power intensity 500 mW/cm 2 for a treatment period of 24 or 48 h) in combination with gentamicin but these effects were not reproducible against Pseudomonas aeruginosa biofilms [89][90][91]. In 2005, Ensing et al [92] also demonstrated greater than 50% reductions in the viability of Escherichia coli biofilms by combining pulsed ultrasound treatment (24-48 kHz, power intensity 500 mW/cm 2 ) with gentamicin.…”
Section: Biofilm Prevention and Control Using Acoustic Energymentioning
confidence: 99%
“…However, it is sometimes deficient in antimicrobial efficacy (21). Many authors have attributed this defect to the incomplete release of the antibiotic from the cement (4,5,6,8,20,23,24). The matrix of polymethylmethacrylate is, to a large extent, impermeable to antibiotics.…”
mentioning
confidence: 99%
“…The subject has been recently reviewed and it was found that both effects depend on factors such as frequency, intensity, materials used for ultrasound diffusion, the presence or absence of cavitation, as well as the type of bacteria [105]. The combined use of therapeutic ultrasound with antibiotics usually decreases bacterial viability in vitro and in vivo [106]. On the other hand, sonication at high frequency is unable to kill bacteria, though some damage to the surrounding tissue is produced [107].…”
Section: Mechanical Action On Biostructuresmentioning
confidence: 99%